ISTRAŽIVANJE UTICAJA I PRIMENE MOLITVE I ASKEZE U SPORTU - Hadži Miloš V. Vidaković (Sport Mont, 2008)
Introduction Minding historical role and significance of Christianity on civilization, it is rightful to except that orthodoxy and Christianity it self remained, and remains today, very deep trace on development of sport. The approach it self to this theme is unusual for more than a reason: the first of all connection between Christianity and sport; the second – this theme is not treated this way until now, and after all it presumed very responsible task and demands the most serious approach. The sample of person’s examinees Doing analysis of gathered results, it was clearly established that significant place belongs to urge need for working on spiritual raising, lifting up ethics and strengthening of faith in Christian –orthodox sense; also of need for life in love with fully respect for other people. Research methods In the research there were used acceptable measure instruments specially prepared for this examination. These methods of statistics analysis’s, method of analyzing the differences, corelational analyses method and applied multivariable methods. Results with discussion Doing analysis results gathered, it was established that significant place belongs to urge need for working on spiritual rising, lifting ethics and strengthening faith in Christian orthodox sense, also for need for life in love with respect for other people. Results of this research pointed on existence of very tight interaction between Christianity and sport as modern time phenomena. The conclusions It ‘s been clearly assured by this research body and mind nature of sport, which is realized in physical and spiritual part of the human being. The wide aspects of urges needed for living can be pleased by the different sights of sport activities, by development and advancing of conscience and Christian feelings through faith, love, prayer, ascetics and fast. The literature 147 Titling units of different authors